Serum levels of matrix metalloproteinase-1 in Brazilian patients with benign prostatic hyperplasia or prostate cancer - El-Chaer, William Khalil (2020)
Metalloproteinases (MMPs) are involved in metastatic tumor processes, with changes in circulating levels detected in several cancer types. Here, we compare serum concentrations of metalloproteinase-1 (MMP-1) across individuals clinically diagnosed with prostate cancer (PCa) or benign prostatic hyperplasia (BPH), correcting results for the rs495366 single nucleotide polymorphism (SNP) that predisposes to differential MMP-1 levels. 196 men aged ≥50 years were followed at a university hospital urology outpatient clinic, with clinical, anthropometric, and rectal examinations performed by one urologist. Blood samples obtained prior to any clinical intervention provided baseline MMP-1 and total/free PSA levels as well as metabolic, hormonal, and inflammatory markers. +e SNP was genotyped by real-time PCR. Participants with medical and/or laboratory profile compatible with malignancy composed the PCa group when confirmed by the Gleason scale. As expected, A-allele homozygotes showed reduced levels of MMP-1. Genotype-adjusted analyses revealed the mean MMP-1 level as 2-fold higher in PCa carriers compared to BPH patients. No other differences were found according to the prostatic condition or genotypic distribution, except for the expected raise in total and free PSA levels in PCa. In conclusion, increased serum levels of MMP-1 were observed in this context of prostatic malignancy compared to a benign phenotype, regardless of a genetic influence.